2015
DOI: 10.1890/14-0391.1
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term declines in nutritional quality of tropical leaves

Abstract: Global change is affecting plant and animal populations and many of the changes are likely subtle and difficult to detect. Based on greenhouse experiments, changes in temperature and rainfall, along with elevated CO2, are expected to impact the nutritional quality of leaves. Here, we show a decline in the quality of tree leaves 15 and 30 years after two previous studies in an undisturbed area of tropical forest in Kibale National Park, Uganda. After 30 years in a sample of multiple individuals of ten tree spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 49 publications
3
40
0
Order By: Relevance
“…First, foods are complex mixtures of many nutrients parcelled at differing ratios, and each nutrient has its 75 Page 2 of 14 own functional implications for the forager . In addition, the nutritional composition of foods varies geographically (Tait et al 2014;Rothman et al 2015). Second, within populations optimal nutrient intake can be variable, for example where nutrient requirements are sex-or age specific Senior et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…First, foods are complex mixtures of many nutrients parcelled at differing ratios, and each nutrient has its 75 Page 2 of 14 own functional implications for the forager . In addition, the nutritional composition of foods varies geographically (Tait et al 2014;Rothman et al 2015). Second, within populations optimal nutrient intake can be variable, for example where nutrient requirements are sex-or age specific Senior et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…If similar declines have occurred at Ngogo, they could have contributed to the red colobus population decline despite the absence of major changes in stem density for these and other important food species (Lwanga et al 2000;Teelen 2008). However, Rothman et al (2015) also noted that the red colobus population in the Kanyawara study area has apparently remained stable during this time, which makes it unlikely that changed leaf quality alone has accounted for the major population decline at Ngogo. Meanwhile, chimpanzee predation on red colobus has been much less intense at Kanyawara than at Ngogo (Gilby and Wrangham 2007).…”
Section: Discussionmentioning
confidence: 96%
“…Concomitantly, the combined hunting rate for other prey species has increased, as has the likelihood that the chimpanzees hunt their main cercopithecoid prey on encounter, mostly because of an increased likelihood of hunting redtails and mangabeys. Rothman et al (2015) documented declines in leaf quality (lower crude protein and high acid detergent fiber content, hence lower protein-to-fiber ratios) over a 15-to 30-yearr period for several tree species important as red colobus food sources at Kanyawara, another site in Kibale ca. 12 km to the north of Ngogo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we examined the CP/NDF ratio of food items from 70 plant species presented to the monkeys. In several primate studies, the protein‐to‐fiber ratio of leaves has been found to be positively correlated with dietary preference (Matsuda et al, 2017; Rothman et al, 2015; Wasserman & Chapman, 2003). We designated food plant species characterized by leaves with a CP/NDF ratio above the mean value of all tested food items as important candidates for ex‐ and in‐situ forest regeneration programs.…”
Section: Methodsmentioning
confidence: 99%